2016
DOI: 10.3390/ph9040076
|View full text |Cite
|
Sign up to set email alerts
|

Applications of High-Throughput Sequencing for In Vitro Selection and Characterization of Aptamers

Abstract: Aptamers are identified through an iterative process of evolutionary selection starting from a random pool containing billions of sequences. Simultaneously to the amplification of high-affinity candidates, the diversity in the pool is exponentially reduced after several rounds of in vitro selection. Until now, cloning and Sanger sequencing of about 100 sequences was usually used to identify the enriched candidates. However, High-Throughput Sequencing (HTS) is now extensively used to replace such low throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…Fewer selection rounds also avoid the potential PCR bias caused by over selection. In addition, global analysis of large sequence datasets by robust bioinformatics tools can further facilitate comprehensive characterization of aptamers, including binding affinity and/or specificity, structure prediction, abundance quantification and aptamer-target interactions [ 42 ]. The first application of high-throughput sequencing in SELEX was performed by Cho M et al in 2010.…”
Section: Limitations and Advancements In Aptamer Selectionmentioning
confidence: 99%
“…Fewer selection rounds also avoid the potential PCR bias caused by over selection. In addition, global analysis of large sequence datasets by robust bioinformatics tools can further facilitate comprehensive characterization of aptamers, including binding affinity and/or specificity, structure prediction, abundance quantification and aptamer-target interactions [ 42 ]. The first application of high-throughput sequencing in SELEX was performed by Cho M et al in 2010.…”
Section: Limitations and Advancements In Aptamer Selectionmentioning
confidence: 99%
“…Sequencing a sample of the population can then identify such sequences. Recently, high-throughput sequencing has led to a better understanding of this molecular evolution process and better identification of the aptamers [9]. The main weakness of RNA and DNA sequences is to be rapidly degraded by nucleases.…”
Section: Introductionmentioning
confidence: 99%
“…HTS is currently known to greatly improve efficiency in analyzing sequences for ssDNA pools, which are generated in the process of SELEX and accurately recognizes highly abundant sequences as aptamer candidates. 5,17 In this study, HTS revealed that PA1, PA2, PA3, PA4, and PA5 (Table 1) were the most abundant sequences in the ssDNA pools from the 9 th , 12 th , and 15 th round of SELEX ( Fig. S1 †); these ve ssDNA sequences were selected as aptamer candidates.…”
Section: Efficient Hts-assisted Recognition Of Aptamer Candidatesmentioning
confidence: 73%
“…15 This rendered the selected aptamer not representative but rather stochastic because of high varieties within more than a million of sequences in the ssDNA pools. 5 Hence, the use of HTS in SELEX greatly assisted the recognition of aptamer candidates with high specicity and efficiency. Table 1 shows that these ve candidates exhibited a much lower free energy (DG) than previously reported aptamers for P. aeruginosa, 10 indicating a greater ease of formatting stable secondary structures.…”
Section: Efficient Hts-assisted Recognition Of Aptamer Candidatesmentioning
confidence: 99%